2014
DOI: 10.1515/nanoph-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Raman scattering in graphene by plasmonic resonant Stokes emission

Abstract: Exploiting surface plasmon polaritons to enhance interactions between graphene and light has recently attracted much interest. In particular, nonlinear optical processes in graphene can be dramatically enhanced and controlled by plasmonic nanostructures. This work demonstrates Raman scattering enhancement in graphene based on plasmonic resonant enhancement of the Stokes emission, and compares this mechanism with the conventional Raman enhancement by resonant pump absorption. Arrays of optical nanoantennas with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…The enhancement factors are evidently maximized where the nanostructures' resonance wavelength coincides with the corresponding G or 2D Stokes wavelength. This confirms that the Raman enhancement mechanism, herein, is dominated by the resonant Stokes emission as previously discussed [18], and the SPP resonances are adequately narrow to resolve the spectral distance between the G and 2D bands. rapidly diminish and the spectra converge to their unperturbed line shapes.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…The enhancement factors are evidently maximized where the nanostructures' resonance wavelength coincides with the corresponding G or 2D Stokes wavelength. This confirms that the Raman enhancement mechanism, herein, is dominated by the resonant Stokes emission as previously discussed [18], and the SPP resonances are adequately narrow to resolve the spectral distance between the G and 2D bands. rapidly diminish and the spectra converge to their unperturbed line shapes.…”
supporting
confidence: 88%
“…This mechanism originates from the enhanced local field produced by the SPP resonances of the nanostructures at the pump laser wavelength, which, in turn, results in the enhancement of Raman scattering due to the nonlinear dependence of the induced optical polarization on the incident field. Moreover, it has been recently demonstrated that utilizing nanostructures whose SPP resonances are tuned to the Stokes wavelengths, rather than the pump wavelength, equally efficiently enhance Raman scattering through an alternative mechanism based on increasing the optical density of states at the emission frequency [18]. This mechanism is similar in nature to the Purcell effect where the increased density of states provided by an electromagnetic cavity enhances the rate of sponta-* ghamsari@uottawa.ca † pberini@uottawa.ca neous emission from a quantum emitter [19].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…where σ intra and σ inter are the intraband and interband terms of the surface conductivity of graphene, τ is the electron-phonon relaxation time, E f is the Fermi energy, and t g is the graphene thickness. The studied metamaterials could be realized in experiment with the help of advanced nanofabrication technology [83]. Firstly, the silver substrate and the silica layer are prepared by thermal evaporation.…”
Section: Methodsmentioning
confidence: 99%